Sustainability‐based value creation within a multi‐stakeholder network: Balancing expectation conflicts within the Amazon context - Dias, Gabriela Nobre; Hamza, Kavita Miadaira; Lievens, Annouk; Moons, Ingrid (Business strategy and the environment, 2025)
The current paper reports on ways to better co‐create sustainability‐based value in multi‐stakeholder networks by focusing on stakeholder expectations, their resulting conflicts, and feasible interventions. Indeed, the literature review reveals a growing research focus on multi‐stakeholder networks involving non‐governmental organizations, traditional communities, and companies operating in vulnerable natural environments. This research interest is driven by the growing need for forest preservation and its impact on creating a more sustainable ecosystem. Our study uses the case of Origens Brasil, a multi‐stakeholder network promoting ethical trade and protection of the Amazon Forest, and involves 47 interviews, and observational data. We contribute by identifying stakeholder expectations and shedding light on the unique conflicts that emerge from differences in these expectations. Furthermore, we developed a framework for sustainability‐based value creation derived from expectation conflict intervening. The current study centers on the question of how to improve the collaborative generation of sustainable value within a multi‐stakeholder network to protect and preserve the Amazon rainforest. Through interviews and observation, our empirical study sought to explore the various types of stakeholder expectations and conflicts, examining their influence on the formation of sustainability‐based value within such networks.